Women’s Reasons for Leaving the Engineering Field - Fouad, Nadya A.; Chang, Wen-Hsin; Wan, Min; Singh, Romila (Frontiers in Psychology, 2017)
Among the different Science, Technology, Engineering, and Math (STEM) fields, engineering continues to have one of the highest rates of attrition (Hewlett, et al., 2008). The turnover rate for women engineers from engineering fields is even higher than for men (Frehill, 2010). Despite increased efforts from researchers, there are still large gaps in our understanding of the reasons that women leave engineering. This study aims to address this gap by examining the reasons why women leave engineering. Specifically, we analyze the reasons for departure given by national sample of 1,464 women engineers who left the profession after having worked in the engineering field. We applied a person-environment fit theoretical lens, in particular, the Theory of Work Adjustment (Dawis & Lofquist, 1984) to understand and categorize the reasons for leaving the engineering field. According to the Theory of Work Adjustment (TWA), occupations have different “reinforcer patterns,” reflected in six occupational values, and a mismatch between the reinforcers provided by the work environment and individuals’ needs may trigger departure from the environment. Given the paucity of literature in this area, we posed research questions to explore the reinforcer pattern of values implicated in women’s decisions to leave the engineering field. We used qualitative analyses to understand, categorize, and code the 1,863 statements that offered a glimpse into the myriad reasons that women offered in describing their decisions to leave the engineering profession. Our results revealed the top three sets of reasons underlying women’s decision to leave the jobs and engineering field were related to: first, poor and/or inequitable compensation, poor working conditions, inflexible and demanding work environment that made work-family balance difficult; second, unmet achievement needs that reflected a dissatisfaction with effective utilization of their math and science skills, and third, unmet needs with regard to lack of recognition at work and adequate opportunities for advancement. Implications of these results for future research as well as the design of effective intervention programs aimed at women engineers’ retention and engagement in engineering are discussed.